Reconstructing the epistemology of classical Islamic dream interpretation: A critical examination of Fakhr al-Dīn al-Rāzī’s Thought in the Book of Mafātīḥ al-Ghayb - Surya, Ilham; Saepul; Darmawangsa; Ramadhani, Ince Atika; Ruhman, Moh Ikhwan Faidlur; Mariadi, Ahmad Mahrus; Hazmin, Moh Minhaji; Agnia Ihsan, Muhamad Wuddy; Imran, Muhammad; Haikal, Muhammad (Research Journal in Advanced Humanities, 2025)
The tradition of dream interpretation in classical Islam developed through a symbolic-transmissionist approach that relied heavily on narrations from the Prophet Muhammad and early scholars. This formed a rigid interpretation pattern and gives less space for rational and contextual approaches. This research aims to analyze and formulate Fakhr al-Dīn al-Rāzī’s thoughts in Mafātīḥ al-Ghayb related to the methodology of dream interpretation. This research is a qualitative study with a library research approach using content analysis and historical-hermeneutic approach to the text of Mafātīḥ al-Ghayb as the primary source. The findings show that al-Rāzī developed a synthesis between spiritual and psychological aspects in interpreting dreams and emphasized the importance of rationality and individual experience in the interpretation process. The approach proposed is systematic-analytical and can be applied across the social and psychological context of the dreamer. Thus, al-Rāzī’s thought offers a new epistemological framework that expands the horizons of dream interpretation in Islam that is more contextual and scientific.